COMPOSITION AND TECHNOLOGY OF PRODUCTION OF HYDROGEL MEDICAL BANDAGES WITH BENTONITE CLAY - BILETSKA, GALANA; STADNYTSKA, NATALIYA; NAZARKO, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article substantiates the composition and production technology of hydrogel medical dressings with bentonite clay. The following composition of hydrogel bandages is proposed: chitosan; polyethylene glycol; bentonite clay modified with argentum ions; hydrochloric acid; water. Chitosan and polyethylene glycol are components of the polymer base. Bentonite clay is simultaneously a component of the polymer base and performs the role of an active substance. As a component of the polymer base, bentonite clay gives the bandage additional strength during stretching and bending, increases its adsorption capacity. The pharmacological effect of bentonite clay determines the anti-inflammatory, hyposensitizing and regenerative properties of hydrogel bandages. Modification of clay with argentum ions ensures the antimicrobial effect of hydrogel bandages. These properties of modified bentonite clay allow not to include medicinal substances in the composition of hydrogel dressings. Hydrochloric acid and water are used as solvents in the production of hydrogel dressings.A method of modification of bentonite clay with argentum ions is proposed, which involves the following stages: grinding, washing and drying of the clay; mixing clay with a solution of argentum (I) nitrate; washing, drying and granulation of modified clay; drying and sintering of granules. It is substantiated that the most optimal method for the production of hydrogel medical bandages with bentonite clay is chemical and radiation. To fill the polymer base of bandages with modified bentonite clay, it is proposed to supplement the technological process with stages during which clay is modified with argentum ions and polymers are mixed with modified bentonite clay.
Keywords: hydrogels; hydrogel medical dressings; chitosan; bentonite clay